Anti-diabetic effects of S. aegyptiaca extract on streptozotocin-nicotinamide induced type 2 diabetes rats - Albosof, Fazel; Hoseini, Sayed Ahmad; Siahpoush, Amir; Malayeri, Ali Reza; Haghighizadeh, Mohammad Hosein (Journal of Contemporary Medical Sciences, 2018)
Objective: Type 2 diabetes mellitus is one the most prevalent disorders worldwide which is associated with unhealthy lifestyle and puts great burden on affected individuals and societies. In addition to chemical drugs and treatment options, using natural products including different types of plant extracts have been in use for curing type 2 diabetes for many years. In this research article we have examined effects of administrating S. aegyptiaca extract on streptozotocin-induced diabetic rats. Methods: Streptozotocin-induced diabetic rats were administrated with 100, 200 and 400 mg/kg of S. aegyptiaca extract or metformin for period of 4 weeks. Blood was taken from animals, and levels of factors including Blood Urea, Cholesterol, Creatinine, HDL, LDL, SGOT, SGPT and Triglyceride were evaluated. Results: Using S. aegyptiaca extract was associated with dramatic changes in lipid profile. It also decreased serum levels of urea, cholesterol and altered activity of SGOT and SGPT enzymes close to normal in treated rats. In comparison with metformin, S. aegyptiaca extract showed more significant results. Conclusion: Results of this study implies that S. aegyptiaca extract can be a good candidate for subsequent studies to define a new natural treatment option for type 2 diabetes mellitus.